tRNA's and priming of RNA-directed DNA synthesis in mouse mammary tumor virus. - Peters, G (1980)
The low-molecular-weight RNAs of mouse mammary tumor virus (MuMTV) were examined by two-dimensional acrylamide gel electrophoresis. Unlike other retroviruses, MuMTV was found to contain only two major fractions of tRNA. These have been fully characterized and shown to correspond to the published sequences for tRNA1+2Lys and tRNA3Lys. By determining which of these tRNA's was most tightly associated with the MuMTV genome and which of them acquired label from [alpha-32P]deoxynucleoside triphosphates in limited DNA synthesis reactions, we identified tRNA3Lys as the primer for MuMTV reverse transcription in vitro. tRNA3Lys does not share any unusual sequence feature with the other previously characterized retrovirus primers, tRNATrp and tRNAPro.